Było, (nie) minęło. Przypomnienie tekstu Tony’ego McEnery’ego i Nicka Ostlera A New Agenda for Corpus Linguistics – Working with All of the World’s Languages - Pacuła, Jarosław (Forum Lingwistyczne, 2020)
In this text I refererate and comment the work from two decades ago. I recall an article important for corpus linguistics – the work of Tony McEnery and Nick Ostler from 2000. In their paper they argue that corpus linguistics needs to expand to cover a wider set of languages. The challenge of building a multilingual corps is admittedly current. The development of corpus linguistics still depends on technical capabilities, but today we see significant changes in this field. In the article I not only present the reflections of British linguists, but I also show current and outdated problems.